Impact of road load parameters on vehicle CO₂ emissions and fuel economy: A case study in Indonesia - Kurnia Fajar Adhi Sukra; Heru Priyanto; Dedy Indriatmono; Muhamad Agus Wijayanto; Irfan Yahya Ikhsanudin; Yoga Akbar Ermansyah (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2023)
Carbon dioxide (CO2) contributes to the greenhouse effect and global warming. The Indonesian government has introduced a reduction in vehicle taxes based on the number of CO2 emissions, meaning that lower CO2 emissions result in lower tax rates. To measure the CO2 emissions, vehicle testing can be conducted on a chassis dynamometer using road load (R/L) parameters to assess the vehicle's loading during the test. The United Nations Economic Commission for Europe (UN ECE) Regulation no. 101 (R101) provides predefined table values for testing, but vehicle manufacturers can also provide their own R/L values, known as actual R/L. In this study, the vehicle underwent two tests: one using the R/L values from the standard table R101 and another using the actual R/L values provided by the manufacturer through coast-down results. By employing the actual R/L values, CO2 emissions can be reduced by up to 7.3 %. This reduction is achieved by lowering the vehicle's load by up to 17 % to enable optimal vehicle performance. Additionally, there is a potential improvement in fuel economy of up to 7.9 % for vehicles. These findings can serve as a reference for establishing future standard testing procedures.